Ordinary Psalms - Levine, Julia B. (Book collections on Project MUSE., 2021)
"Struggling to accept her impending blindness, the speaker in Julia B. Levine's fifth collection of poetry, "Ordinary Psalms," asks the everyday world to help her learn how to see beyond appearances into the fundamental truth of vision. As she contemplates the loss of one friend to cancer and another to suicide, along with her own visual impairment, Levine holds the world "close as I needed to see." Imagistic, lyrical, and at times imploring divine intervention from a god she does not know or trust, these poems curse and praise the extraordinary world we live in and are in danger of losing. Lamenting that "this world is a mortal affliction with wounds in the beautiful," "Ordinary Psalms" provides a seductive and lyric rumination on beauty, loss, and grief"--